A figuração da história em Boitempo, de Carlos Drummond de Andrade - Henrique Barros Ferreira (2018)
The propose of this work is to develop a research about the Boitempo (1968) of Carlos Drummond de Andrade, from a materialist perspective which deals with dialetic relations between the literature and the social process. As a starting point, we will seek to understand the constitution of the modern lyric, giving evidence to the concept of romantic irony, that will behave as the reading key of the book. In a second moment, we will research how the drummondian memorialism engender a lyrical form on it's own, which operates on the limits of history and fiction. On the last, we will analyse how the poems recover the history from a critcal perspective, originating contradictory points of view inside the same social dynamics. In this sense, our interpretation starts at the stilistic choices and the objective conformation of the poems, where the questions to be developed are sedimented.